Urban apologetics : restoring Black dignity with the gospel - Mason, Eric, (Eric M.) (Grand Rapids Zondervan reflective, 2021)
"Urban Apologetics equips pastors, churches, and everyday believers to engage, understand, and love African Americans who are involved in ethnocentric ideologies and black mystery cults"--
Includes index.
Keywords: African Americans -- Religion; African American churches; African American women -- Conduct of life; Church work with African Americans